Quality measurements affected by frozen storage of fishes - Kumar , Sanoj (Journal of Postharvest Technology, 2017)
Fish is a very perishable food and therefore several storage strategies need to be employed to increase its shelf-life, guaranteeing its safety and quality from catch to consumption. Despite the advances in modern fish storage technologies, chilling and freezing are still the most common preservation methods used onboard. The present review aims to summarize strategies to increase the shelf-life of fresh (chilled) and frozen fish. Although there are other factors that influence the fish shelf-life, such as the fish species and the stress suffered during catch, storage time and temperature and the amount of ice are some of the most important. In addition, the way that fish is stored (whole, fillet, or gutted) also contributes to the final quality of the product. A major problem with food storage, whether refrigeration or freezing, is quality degradation. Major physical and chemical attributes affected in fish are color, texture, enzymatic activity, lipid oxidation, and ice crystal structural damage. Storage time, whether that is short or long term, affects these quality attributes in different ways.